Analisis Pengaruh Influencer Terhadap Keputusan Pembelian Skincare dan Make Up di Kalangan GenZ - Alya Syafira Khairunnisa; Balqis Najmi Aqila Putri Syaela; Firda Nur Fauziah; Hasna Maisya Nazhirah; Myisha Azlia Nafhatus Sofa; Najma Silma Nayyara; Rama Wijaya Abdul Rozak (Jurnal Mahasiswa Kreatif, 2024)
This research analyzes the influence of influencers on purchasing decisions for skincare and makeup products among Generation Z. Data was collected through a questionnaire distributed to 170 respondents. The results show that most of Generation Z follows influencers' social media accounts to obtain product information and recommendations. Influencer reviews have a significant influence on purchasing decisions, with 85.9% of respondents being interested in buying products after seeing influencer reviews. However, 88.8% of respondents still conduct additional research before making a purchase. The presence of influencer reviews can trigger consumptive behavior, with 69.4% of respondents stating so. To overcome this behavior, 87.6% of respondents set a special budget, and 89.4% compare product prices. Nevertheless, 64.1% of respondents spent more than their planned budget, with 60.6% spending more than IDR 200,000 per month on skincare and makeup products. This research concludes that influencers have a significant influence in attracting purchase interest and purchasing decisions among Generation Z for skincare and makeup products.